Commentaries on Pindar - Verdenius, W. J. (Mnemosyne, Supplements, 1987)
This volume contains word-for-word commentaries on Pindar's Olympian Odes 3, 7, 12, 14. Emphasis is placed on the explanations of peculiarities of grammar and idiom, but due attention is paid to figures of style and problems of poetic structure. The interpretations proposed by the author - many of them which are new - are documented as fully, but at the same time as concisely, as possible. This documentation, which includes a critical examination of other views, has been made more easily accessible by detailed indexes. The poems discussed do not have special similarities or interrelationships. On the other hand, they may be considered representative of the poet's art. From this point of view, the present selection may serve as an introduction to the study of Pindar's work. Vol. II will contain commentaries on Olympians 1, 10, 11, Nemean 11, and Isthmian 2. A third volume on Pythians 1, 8, 10 is inteded to conclude the series.